2021
DOI: 10.31219/osf.io/zxg83
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation into the rationale of migration intention due to air pollution integrating the Homo Oeconomicus traits

Abstract: Air pollution is a considerable environmental stressor for urban residents in developing countries. Perceived health risks of air pollution might induce migration intention among inhabitants. The current study employed the Bayesian Mindsponge Framework (BMF) to investigate the rationale behind the domestic and international migration intentions among 475 inhabitants in Hanoi, Vietnam – one of the most polluted capital cities worldwide. We found that people perceiving more impacts of air pollution in their dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Nevertheless, educational level is only one of many factors that must be considered when pondering upon a lifetime decision, like migration. Vuong, Le, Nguyen, and Nguyen [ 51 ] suggested that some traits of Homo oeconomicus , who always acts to maximize the economic benefits, might also affect the inhabitants’ migration consideration due to air pollution. Some distance costs (e.g., finance, culture shock) exist when migrating to a new place [ 65 , 66 ], so younger, highly educated people would have more time to regain such loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, educational level is only one of many factors that must be considered when pondering upon a lifetime decision, like migration. Vuong, Le, Nguyen, and Nguyen [ 51 ] suggested that some traits of Homo oeconomicus , who always acts to maximize the economic benefits, might also affect the inhabitants’ migration consideration due to air pollution. Some distance costs (e.g., finance, culture shock) exist when migrating to a new place [ 65 , 66 ], so younger, highly educated people would have more time to regain such loss.…”
Section: Discussionmentioning
confidence: 99%
“…BMF utilizes the mindsponge mechanism of information processing as the theoretical foundation and employs Bayesian inference to construct statistical analysis. Since its original conception [ 49 , 50 ], the mindsponge mechanism has been expanded and proven to be effective in explaining how ideation occurs in the human mind based on subjective cost-benefit evaluation [ 48 , 51 ]. It is also essential when dealing with complex information processes [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…There have been many studies carried out to find out the impact of air pollution on the lives of people in the urban cities [7,8], which inspire to conduct this study. This study is a part of assignment project of Introduction to Statistics and Probabilities class, which attempts to enlighten up the fact as to why the local government should take steps to improve the air quality and also verifies the effects of population migration caused by air pollution.…”
Section: Introductionmentioning
confidence: 99%